Genetic Diversity of the Haliotis diversificolor squamata from Southern Coastal Java (Banten, Pangandaran and Alas Purwo) and Bali Based on Mitochondrial CO1 Sequences - Syamsul Bachry; Dedy Solihin; Rudhy Gustiano; Kadarwan Soewardi; Nurlisa Butet (Tropical Life Sciences Research, 2019)
The morphology of Haliotis genus is very difficult to distinguish because of its high similarity. Therefore, an identification tool such as genetics is needed to distinguish the genus. This study describes molecular characters of a species of Haliotis (Mollusca: Gastropoda: Haliotidae) from the southern Java and Bali waters, Indonesia, that is currently considered to be a subspecies of another occurring in China, Taiwan and Japan. DNA of Haliotis specimens collected from southern Java and Bali waters was extracted from epipodial tissues using a DNeasy® Blood and Tissue Kit, and partial CO1 genes amplified using AB-CO1DivF and AB-CO1DivR primers. Genetic distances were determined by Kimura 2-parameter, and phylogenetic trees constructed using the Neighbor-joining method in MEGA 5.0 software. Based on the genetic distance using the COI mtDNA gene as a barcoding species, the difference was 15.9%–16.7% with H. diversicolor superteksta from China, H. diversicolor from Taiwan (7.73%–9.12%), and H. diversicolor from Japan (7.80%–9.20%), because of boundary for determining species groups based on of 4% and mollusks at 4.8%, then H. diversicolor squamata spread in the southern islands of Java and Bali is worthy of being separated into its own species. From the results of this study, we propose that abalone from the south of Java and Bali waters became a separate species, H. squamata Reeve 1846. While percentage difference in interpopulation genetic distance from Java and Bali about 0.000%–0.011% or 0.0%–0.11%, averaging 0.60%.